A Modified Super-linear QN-Algorithm for Unconstrained Optimization - Abbas Y. AL-Bayati; Ivan Subhi Latif (المجلة العراقية للعلوم الاحصائية, 2010)
In this paper, we have proposed a modified QN-algorithm for solving a self-scaling large scale unconstrained optimization problems based on a new QN-update. The performance of the proposed algorithm is better than that used by Wei, Li, Yuan algorithm. Our numerical tests show that the new proposed algorithm seems to converge faster as compared with a standard similar algorithm in many situations .